2019
DOI: 10.1038/s41563-019-0340-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale ordering in highly stretchable polymer semiconducting films

Abstract: Stretchable semiconducting polymers have been developed as a key component   to enable skin-like wearable electronics, but their electrical performance must be improved to enable more advanced functionalities. Here, we report a solution processing approach that can achieve multi-scale ordering and alignment of conjugated polymers in stretchable semiconductors to substantially improve their charge carrier mobility. Using solution shearing with a patterned microtrench coating blade, macroscale alignment of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
357
2
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 308 publications
(370 citation statements)
references
References 33 publications
6
357
2
5
Order By: Relevance
“…Inspired by the sensory system, researchers integrated flexible electronics to acquire the signals and transmitted the acquired signals to motor nerves to actuate muscles . Intrinsically stretchable organic conductors and semiconductors are highly desirable for applications in signals transmitting and processing . For example, Wang et al demonstrated a stretchable transistor array by using intrinsically stretchable conducting and semiconducting polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the sensory system, researchers integrated flexible electronics to acquire the signals and transmitted the acquired signals to motor nerves to actuate muscles . Intrinsically stretchable organic conductors and semiconductors are highly desirable for applications in signals transmitting and processing . For example, Wang et al demonstrated a stretchable transistor array by using intrinsically stretchable conducting and semiconducting polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, mass transport is greatly enhanced through vertically aligned channels due to the low tortuosity. Inspired by nature, considerable efforts focused on the design of aligned micrometer‐scale porous structures, showing promising applications in electronics, biomedical engineering, and energy storage devices . Solid electrolyte with aligned structures exhibits low tortuosity and thus facilitates high ionic transfer, comparable to bare liquid electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Rational molecular design of conjugated polymers is crucial for tuning molecular self‐organization behavior in the solid state and consequently for improving the performance and stability of organic light‐emitting diodes (OLEDs), organic solar cells (OSCs), organic field‐effect transistors (OFETs), and organic lasers (OLs) . Interchain π–π interaction plays a central role in polymer‐based optoelectronic because of the dense aromatic packing leading to oriented superstructures that enable efficient exciton and charge transport, however, its effect on light emission is often detrimental due to the formation of non/weakly emissive intermolecular excited states such as polaron pairs or excimers and aggregation‐caused quenching (ACQ) . What's more, multiple secondary noncovalent interactions resulting from heavy heteroatom substitution and rigid aromatic polymer backbones can facilitate compact interchain packing, which consequently affect the film morphology, energy bandgap, photoluminescence (PL) color purity, and light emission efficiency .…”
Section: Introductionmentioning
confidence: 99%